Productive safety management a strategic, multi-disciplinary management system for hazardous industries that ties safety and production together - Mol, Tania (Boston, MA : Butterworth-Heinemann, 2003)
Unlike most books on this subject, Productive Safety Management, described in this book, integrates occupational health and safety, human resource management, environmental management, and engineering to provide a whole-business approach to effective safety management. The book helps companies to reduce and manage risk by providing, analysing and improving systems in place within the company. It also looks at how external factors can affect company decision making and provides a tool to make sure that a health and safety management system is strategically aligned, appropriately resourced, and that it maximises employee commitment. Chapters on human resource management explore cultural issues and explain how to gain commitment to company objectives. The book has been written for managers and supervisors working in hazardous industries, OHS practitioners, undergraduate and postgraduate students. * Provides a management system that allows production, safety and quality to be pursued concurrently in hazardous industries * Improves risk management so that the incidence of injury and damage is minimized * Describes, using practical examples, the sources of risk in hazardous industries and how these can be managed.
Risk : can it be eliminated? -- Organization decision-making and alignment of management systems -- Processes -- Technology -- Physical environment -- Human resources -- Risk quantification and strategy development -- Management commitment and leadership -- Training : building the organization's capacity -- Behavioral audits -- Formulating the productive safety management plan -- Managing performance using the achievement cycle.
Includes bibliographical references and index.
Keywords: Industrial safety -- Management; Industrial safety -- Planning; Risk management; Electronic books